Perovskite-Like Pr(A)MnO3 (A = Ca, Sr) as Anode Materials for Solid Oxide Fuel-Assisted Electrolysis Cells - Yaremchenko, Aleksey (2022)
Long-term degradation remains the main issue for the viability of solid oxide electrolysis cell (SOEC) technology as a practical hydrogen production system. One of the main specific degradation mechanisms in SOECs relates to the delamination phenomena at or near the electrolyte/anode interface. The principle of so-called fuel-assisted electrolysis is to supply the carbon-containing species which can react with oxygen at the anode side thus bringing down the oxygen chemical potential at the electrolyte/anode interface and improving its stability. The present work is aimed at the characterization of PrMnO3-based perovskites for potential application as anodes in solid oxide fuel-assisted electrolysis cells. Pr0.60-xA0.40MnO3±δ (A = Sr, Ca; x = 0 and 0.05) were synthesized by glycine-nitrate combustion technique. The characterization included XRD, SEM/EDS, XPS, dilatometry and thermogravimetry, measurements of electrical properties and oxygen permeability, and determination of oxygen nonstoichiometry. XRD analysis confirmed the formation of solid solutions with orthorhombic perovskite structure. The oxides exhibit negligible variations of oxygen content under oxidizing conditions while reducing p(O2) below 10-4 atm results in oxygen losses from the lattice and reduction of Mn cations. XPS results suggest that praseodymium remains in a 3+ oxidation state in the bulk of ceramics but may adopt a mixed 3+/4+ oxidation state at the surface. The lowp(O2) stability boundary of the perovskite phase at 800°C corresponds to ~10-17-10-16 atm; the stability domain is wider for Ca-substituted compositions and narrows with the introduction of A-site vacancies. Dilatometric studies confirmed good thermomechanical compatibility with common solid electrolytes under oxidizing conditions; however, reduction at operation temperatures (800°C) leads to undesirable chemical expansion. The electrical conductivity of Pr0.60-xA0.40MnO3±δ ceramics is p-type electronic and decreases with reducing p(O2) but still exceeds 40-50 S/cm under anticipated oxygen electrode operation conditions. The electrochemical activity of Pr0.6-xA0.4MnO3±δ electrodes was evaluated in contact with yttria-stabilized zirconia solid electrolyte as a function of relevant parameters (fabrication conditions, with and without buffer layers, with modifications via infiltration of praseodymia and/or doped ceria). The best performance was obtained for the cells with Pr0.55A0.40MnO3±δ electrodes (gadolinia-doped ceria buffer layers, PrOy load of ~33 wt.%) that showed anodic overpotential of around 50 mV under 500 mA/cm2 at 800°C in air.